Pendidikan Agama Islam untuk Good Corporate Governance - Eka Firmansyah; Tobroni Tobroni; Romelah Romelah (Edukasi Islami: Jurnal Pendidikan Islam, 2012)
Good Corporate Governance in Indonesia has become our concern especially as a moslem manpower who work there. It is, tehrefore our responsibility to address moslem manpower as the main agenda of our development at school and campus.Curriculum of Islamic Religion at Vocational High School has become priority in our strategy, plan, and policy. This should make all element be active by involved and it include Islamic Education Institutions.Moslem manpower needs vision and political will and commitment from all social component sucah as moslem individual (including parent), scientiest, religion scholar’s as well as education institution. Without political will and united efforts the moslem manpower will be left behind.Key word : Islamic Education Institution, moslem manpower, motivation, productivity, quality, and industry